State, society, and land in Jordan - Fischbach, Michael R. (Brill, 2000)
Examines how state and society conceptualized land ownership in Jordan from the late Ottoman era through the 1950s, and how the resulting interaction between them shaped the socio-economic and political contours of modern Jordan.
Keywords: Land tenure -- Jordan -- History -- 19th century.; Land tenure -- Jordan -- History -- 20th century.; Land use -- Jordan -- History -- 19th century.; Land use -- Jordan -- History -- 20th century.; Land value taxation -- History -- 19th century.; Land value taxation -- History -- 20th century.; Utilisation du sol -- Jordanie -- Histoire -- 19e siècle.; Utilisation du sol -- Jordanie -- Histoire -- 20e siècle.; Propriété foncière -- Impôts -- Histoire -- 19e siècle.; Propriété foncière -- Impôts -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Real Estate -- General.; Land tenure; Land use; Land value taxation; Jordan; Grundeigentum; Sozioökonomischer Wandel; Jordanien; Grondpolitiek.; Grondbezit.; 1800-1999; History